A Rare Case of Familial Neurogenic Diabetes Insipidus in a 22-Year-Old Man - Van T.T. Phan, MD; Zachary W. Bloomer, MD; Vien T.X. Phan, PhD; Mohamed K.M. Shakir, MD; Thanh D. Hoang, DO (AACE Clinical Case Reports, 2021)
Objective: Diabetes insipidus (DI) can be classified into 2 types: central/neurogenic DI and nephrogenic DI. Most cases of central DI occur after brain surgery, trauma, tumor, or infection. Here we report a rare case of familial central DI due to a heterozygous AVP gene mutation. Methods: A case of familial neurogenic DI has been described with thorough clinical, laboratory, and genetic workup. PubMed and Google scholar databases were used for literature discussion. Results: A 22-year-old man presented with polyuria and polydipsia. He drank about 4 gallons of water everyday and urinated large volumes very frequently. His physical examination was unremarkable. After 2 hours of water-deprivation, his serum sodium level was 147 mmol/L, serum osmolality was 302 mOsm/kg with concurrent urine osmolality of 78 mOsm/kg, vasopressin level was <0.8 pg/mL, and copeptin level was <2.8 pmol/L, suggesting neurogenic DI. His brain magnetic resonance imaging revealed the absence of the posterior pituitary bright spot but a normal anterior pituitary gland. Genetic analysis revealed a nonfunctional heterozygous mutation in the AVP gene. Further questioning revealed that his mother also had the disease and that he had been treated with desmopressin as a child; however, it was later self-stopped. The patient was reinitiated on desmopressin, which improved his symptoms. Conclusion: Genetic mutations in the AVP gene represent a very rare etiology of DI, and patients with DI respond well to desmopressin treatment.